THE EFFECT OF INTRAPRENEURIAL COMPETENCIES ON INNOVATIVE WORK BEHAVIOUR: A CASE OF CYBER SECURITY EXPERTS IN MALAYSIA - Neerosha Raja, Amir Aris, Haslinda Musa (International Journal of Advanced Science and Technology, 2020)
In today's world, more attention is paid to innovation, which is a way of responding to global competition and environmental pressures. Employees play a crucial role in the process of innovation, as they are the foundation of ideas. Innovative work behaviour is therefore of interest when organisations are focused on innovation. Researchers wanted to gain more insight into the innovation process because of the decline in organisational innovation capacity as is the case for critical information infrastructure; cyber security. As a result, this study is designed to investigate intrapreneurial competencies that foster employees' innovative work behaviour. This paper suggests a conceptual model for further understanding of the relationship between intrapreneurial competencies and innovative work behaviour. This paper is then developed for future studies into a concrete research hypothesis. This research is proposed in the hope that the findings of the researcher will report a significant relationship between intrapreneurial competencies and innovative work behaviour.